STRATEGY TO INCREASE ANNUAL PREMIUM EQUIVALENT (APE) FROM BANCASSURANCE PRODUCTS AT BCA REGIONAL OFFICE V MEDAN - Pinta Serli Waty Lumban Toruan; Nazaruddin; Meilita Tryana Sembiring (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study discusses strategies to increase Annual Premium Equivalent (APE) for bancassurance products at BCA Regional Office V Medan. The main focus is to utilize internal strengths, such as digital technology through BCA Mobile, to support efficient distribution and expand product reach. The analysis shows opportunities from increasing public awareness of the importance of insurance, supported by financial inclusion and technological developments. However, tight competition and stricter regulations are challenges that need to be overcome with product innovation, customer education, and the use of big data to personalize offers. The strategy involves strategic collaboration with agents and brokers, as well as optimizing digital channels for marketing and distribution. The resulting recommendations can significantly increase APE through product diversification and expansion of distribution networks, while also responding to the needs of the growing market.